ANALISIS KEMAMPUAN ADAPTASI TEKNOLOGI DAN LITERASI MEMBACA SEBAGAI KESIAPAN MENGHADAPI ERA NEW NORMAL DALAM IMPLEMENTASI PROGRAM KAMPUS MENGAJAR - Prastowo, Dedi Catur; Riswanto, Riswanto; Alarifin, Dedy Hidayatullah (JURNAL FIRNAS, 2023)
Abstract: This study aims to determine and conclude about the readiness or unpreparedness of the fifth grade UPTD SD Negeri 2 Mekarmukti students in the new normal when viewed from their reading literacy ability. As well as knowing and concluding about the readiness or unpreparedness of the fifth grade school teacher in the new normal when viewed from the ability to adapt to technology. This type of research is a case study using a qualitative research approach. The process of collecting data using the Snowball, then the technique is packaged into a data triangulation method with the help of three instruments, namely observation, interviews, and questionnaires. The data triangulation method is used by researchers to make it easier to draw conclusions obtained through the validity and saturation of the data obtained through the three data collection instruments that have been used. Based on the results of the analysis of the three instruments that have been triangulated and verified by the researcher, the fifth grade students are ready to face learning in the new normal based on the National Assessment if viewed from reading literacy. This readiness can be proven by 2 (two) of 3 (three) students, having met the indicators of reading literacy ability, namely the ability to read and students' understanding of a reading. While the last one student, does not yet have good reading literacy skills because they have not met these two indicators. Then on the ability to adapt to technology, the fifth grade teacher of the school already has the readiness to face learning in the new normal when viewed from the ability to adapt to technology. This readiness can be seen from self-knowledge of technology that is very good and has an interest in utilizing technology in the offline learning process in the classroom on an ongoing basis.